Resident Challenges With Pain and Functional Limitations in Chinese Residential Care Facilities. (8th December 2018) - Song, Yuting; Anderson, Ruth A; Wu, Bei; Scales, Kezia; McConnell, Eleanor; Leung, Angela Y M; Corazzini, Kirsten N
Abstract: Background and Objectives: Pain and functional limitations can severely impede older adults' quality of life. In Chinese residential care facilities, limited research suggests that residents potentially have significant unmet care needs with pain and related functional limitations. Therefore, we aimed to explore residents' challenges and self-management strategies in these two areas. This knowledge is essential to developing care interventions to improve quality of care and quality of life in Chinese residential care facilities. Research Design and Methods: We conducted semi-structured open-ended interviews with residents ( n = 21) in two facilities in eastern and central China and assessed their pain and functional status using self-report measures from Minimum Data Set 3.0. We applied descriptive statistics to the self-reported data and analyzed the interview data using thematic analysis by drawing on the Adaptive Leadership Framework. This framework proposes that individuals living with chronic conditions need to engage in work to address their complex health concerns and that they need support from the environment to facilitate problem-solving. Results: Residents described significant unmet care needs with pain and functional limitations. To address these care needs, they adopted a substantial number of self-management strategies. While doing so, they faced significant barriers, including service gaps and inadequate direct care. Discussion and Implications: The findings suggest further research to explore long-term care policy change that is needed to provide comprehensive health and medical services and adequate direct care in these facilities. The importance of establishing various types of long-term care facilities is also highlighted.